Diffusion of Methylene Blue in Phantoms of Agar Using Optical Absorption Techniques - Vilca-Quispe, Lidia; Castilla-Loeza, Alejandro; Alvarado-Gil, Juan José; Quintana-Owen, Patricia (IntechOpen, 2011)
None